-3*x+15=-6

Simple and best practice solution for -3*x+15=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3*x+15=-6 equation:


Simplifying
-3x + 15 = -6

Reorder the terms:
15 + -3x = -6

Solving
15 + -3x = -6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + -3x = -6 + -15

Combine like terms: 15 + -15 = 0
0 + -3x = -6 + -15
-3x = -6 + -15

Combine like terms: -6 + -15 = -21
-3x = -21

Divide each side by '-3'.
x = 7

Simplifying
x = 7

See similar equations:

| 3-20=g | | 9t+31=184 | | 5t-4=3t-6 | | 3n(3n+4)=0 | | 9t+31= | | 63x(-9)=t | | 9x-36= | | 8w^2+30w-27=0 | | N-3/7=21 | | 4-u/5=0 | | -24=-4m | | 56x^2-47x+5=0 | | 2(3x+11)=6x/3+4 | | 8p/2+12/2=50 | | 26.50+0.15=1450+0.25 | | 6+4x-4=3x-6-x | | -25=16+c | | 150X+200+50X+100= | | A^2-19A-20=0 | | 1/4+2/5n=41/4 | | 9g+14=2g | | x-22=-15 | | x-(9)=-33 | | 7(P-2)=32 | | 16.85-x=6x | | 4x+16=2x/4 | | 3z-32=-7z+28 | | 6(k^2-2k)=0 | | d(2d+4)-6=2d^2+3d+6 | | 58=t+23 | | 6/(g+2)=1 | | 28=m-7 |

Equations solver categories